Photocatalytic activity of TiO2/stevensite nanocomposites for the removal of Orange G from aqueous solutions. (June 2014) - Bouna, L.; Rhouta, B.; Maury, F.; Jada, A.; Senocq, F.; Lafont, M. -C.
Abstract: TiO 2 /stevensite nanocomposite photocatalysts were synthesized by a solvothermal method using TiCl3/HCl as reactants and the stevensite clay mineral extract as support. The prepared photocatalyst samples were then characterized using various techniques such as X-ray diffraction (XRD), Infrared spectroscopy (IR) and Transmission Electron Microscopy (TEM). The Points of Zero Charge (PZC) of the various samples were evaluated by titration of the non-modified and the Ti-modified clay aqueous dispersions, with cationic surfactant solutions. The photocatalytic activity of the resulting nanocomposites samples were evaluated for the removal of Orange G (OG) from aqueous solution as a model dye pollutant. The data indicate that the formation of Na + -stevensite by the TiO 2 particles leads to TiO 2 /stevensite nanocomposites having higher specific surface areas and mesopore volumes, and lower PZC values. Further, the photocatalytic activity was greater for the TiO 2 /stevensite nanocomposites having the greatest Ti amount, as compared to a pure TiO 2 sample, and increased with the increase of the TiO 2 content in the TiO 2 /stevensite nanocomposites.